Catalytic pyrolysis of waste high-density (HDPE) and low-density polyethylene (LDPE) to produce liquid hydrocarbon using silica-alumina catalyst (Journal of Bangladesh Academy of Sciences, 2023)
Catalytic pyrolysis of waste HDPE and LDPE polyethylene was successfully carried out using a silica-alumina catalyst at 450 °C under N2 atmosphere. The synthesized silica-alumina is mesoporous and shows type IV isotherm. Thermal pyrolysis (without any catalyst) provided 47% wax-like hydrocarbons at 485 °C. On the other hand, more than 80% liquid yield was achieved using silica-alumina catalysts from waste HDPE and LDPE. The highest liquid yield was obtained from LDPE (87.69%) than HDPE (83.25%) at a catalyst-to-plastic ratio of 1:25. The 1H NMR shows that the liquid product does not contain any aromatic compound. The GC-MS, 1H NMR, and FTIR confirmed that the liquid contains linear and branched alkanes and alkenes.J. Bangladesh Acad. Sci. 47(2); 195-203: December 2023